An accurate and convenient method for Mycoplasma pneumoniae via one-step LAMP-CRISPR/Cas12b detection platform - Liu, Tao; Liu, Qing; Chen, Fuqun; Shi, Ying; Maimaiti, Guliya; Yang, Zhanhua; Zheng, Shutao; Lu, Xiaomei; Li, Hui; Chen, Zhaoyun (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionMycoplasma pneumoniae (MP) is the major cause of respiratory infections that threaten the health of children and adolescents worldwide. Therefore, an early, simple, and accurate detection approach for MP is critical to prevent outbreaks of MP-induced community-acquired pneumonia.MethodsHere, we explored a simple and accurate method for MP identification that combines loop-mediated isothermal amplification (LAMP) with the CRISPR/Cas12b assay in a one-pot reaction.ResultsIn the current study, the whole reaction was completed within 1 h at a constant temperature of 57°C. The limit of detection of this assay was 33.7 copies per reaction. The specificity of the LAMP-CRISPR/Cas12b method was 100%, without any cross-reactivity with other pathogens. Overall, 272 clinical samples were used to evaluate the clinical performance of LAMP-CRISPR/Cas12b. Compared with the gold standard results from real-time PCR, the present method provided a sensitivity of 88.11% (126/143), specificity of 100% (129/129), and consistency of 93.75% (255/272).DiscussionTaken together, our preliminary results illustrate that the LAMP-CRISPR/Cas12b method is a simple and reliable tool for MP diagnosis that can be performed in resource-limited regions.